Analysis of proteins in the spent culture medium of Lupinus albus by electrospray ionisation tandem mass spectrometry - Schwend, Thomas; Ruppert, Thomas; Szenthe, Andrea; Wink, Michael (Journal of chromatography, 2003)
Lupinus albus cell cultures secrete a large set of hydrolases into their medium with a small number of highly abundant proteins. We have investigated the protein composition of the medium with two different methods, two-dimensional gel electrophoresis-electrospray ionisation tandem mass spectrometry (ESI-MS-MS) and enzymatic analysis. The proteomic approach revealed the presence of several abundant proteins that had been overlooked using standard enzyme assays, e.g. subtilisin-like protease, glucan 1,3-β-glucosidase, α-amylase, chitinase, thaumatin-like protein, and a secretory pathogenesis-related protein. Several low-abundant proteins were readily detectable by enzymatic assays (peroxidases, phosphatase), but could not be found by ESI-MS-MS. Both data sets support the assumed lytic function of the medium, which appears to be similar to that of the plant vacuole.